Robust decentralized model predictive control approach for a multi-compressor system surge instability including piping acoustic. Issue 1 (1st January 2018) - Imani, Hashem; Jahed-Motlagh, Mohammad Reza; Salahshoor, Karim; Ramezani, Amin; Moarefianpur, Ali
Abstract: One of the major problems in modern gas compressing stations is related to surge control of compression system with multi-compressor. Due to the coupled system dynamics, standard controllers can interfere with each unit′s performance. This article introduces a new robust decentralized model predictive control (MPC) scheme for a team of cooperating compressors. In the decentralized control strategy, the integration of H∞ control scheme into a robust tube MPC algorithm is used to solve the surge problem of a multi-compressor dynamical process subject to constraints in a computation efficient way. Nonlinear dynamic for each compressor that contains acoustic of compressor system is considered and brings up the effects of the station's piping system on the compressor surge Numerical simulations approve the capability of the proposed surge control method and guaranty the asymptotic stability of compression system in the presence of disturbances and coupling effects.